(untitled) (Revista revoluciones, 2024)
The implementation of water harvesting and irrigation techniques represents a viable solution to the dual challenges of the water crisis and food insecurity. These techniques integrate local knowledge with ancestral technologies based on natural water recharge infrastructure. Nevertheless, the excessive use of the term has resulted in its original meaning being obscured, leading to confusion with conventional hydraulic technologies. In this context, the present manuscript examines and discusses a conceptual approach to the aforementioned category. The methodology entailed a review of documents retrieved from various search engines, including Google Scholar, Scopus, Web of Science, Scielo, and others. The results indicate that the practice of water planting and harvesting is known by different names in different territories, reflecting the diverse adaptations and developments of this technology. In conceptualizing this practice, it is primarily associated with natural infrastructures. However, some authors differentiate between planting and harvesting water as distinct actions. Despite these nuances, it can be concluded that planting and harvesting water is a practice rooted in traditional ecological knowledge, transmitted, inherited, and reproduced in the territories of indigenous peoples and peasants.